Prevention of congenital chagas disease by trypanocide treatment in women of reproductive age: A meta-analysis of observational studies. - Francisco Cezar Aquino de Moraes; Maria Eduarda Cavalcanti Souza; Lucca Dal Moro; Isabelle Batista Donadon; Emanuele Rocha da Silva; Dilma do Socorro Moraes de Souza; Rommel Mario Rodríguez Burbano (Public Library of Science (PLoS), 2024)
Background Maternal-foetal transmission of Chagas disease (CD) affects newborns worldwide. Although Benznidazole and Nifurtimox therapies are the standard treatments, their use during pregnancy is contra-indicated. The effectiveness of trypanocidal medications in preventing congenital Chagas Disease (cCD) in the offsprings of women diagnosed with CD was highly suggested by other studies. Methods We performed a systematic review and meta-analysis of studies evaluating the effectiveness of treatment for CD in women of childbearing age and reporting frequencies of cCD in their children. PubMed, Scopus, Web of Science, Cochrane Library, and LILACS databases were systematically searched. Statistical analysis was performed using Rstudio 4.2 using DerSimonian and Laird random-effects models. Heterogeneity was examined with the Cochran Q test and I2 statistics. A p-value of <0.05 was considered statistically significant. Results Six studies were included, comprising 744 children, of whom 286 (38.4%) were born from women previously treated with Benznidazole or Nifurtimox, trypanocidal agents. The primary outcome of the proportion of children who were seropositive for cCD, confirmed by serology, was signigicantly lower among women who were previously treated with no congenital transmission registered (OR 0.05; 95% Cl 0.01-0.27; p = 0.000432; I2 = 0%). In women previously treated with trypanocidal drugs, the pooled prevalence of cCD was 0.0% (95% Cl 0-0.91%; I2 = 0%), our meta-analysis confirms the excellent effectiveness of this treatment. The prevalence of adverse events in women previously treated with antitrypanocidal therapies was 14.01% (95% CI 1.87-26.14%; I2 = 80%), Benznidazole had a higher incidence of side effects than Nifurtimox (76% vs 24%). Conclusion The use of trypanocidal therapy in women at reproductive age with CD is an effective strategy for the prevention of cCD, with a complete elimination of congenital transmission of Trypanosoma cruzi in treated vs untreated infected women.